Pemilihan Pengangkatan Karyawan Tetap Menerapkan Metode Multi-Attributive Border Approximation Area Comparison - Fitri Laila; Nelly Astuti Hasibuan (Journal of Informatics Management and Information Technology, 2021)
The selection procedure determines permanent employees at PT Siantar Top, Tbk, starting with employees who volunteer and want to work as permanent employees at PT Siantar Top, Tbk. Next, fill in the personal data form, then a selection will be carried out with an assessment of several aspects such as GPA, Age, Basic Ability, Psychological Test, and Work Experience. The problem that occurs in this case is that PT Siantar Top, Tbk is difficult to make decisions in determining permanent employees. In this study, to resolve these problems the authors designed a decision support system for determining permanent employees at PT Siantar Top, Tbk. by applying the Multi-Attributive Border Approximation Area Comparison (MABAC) Method. The design of this system is made using the Visual Basic Net 2008 programming language and the MySQL database as a storage place for data entered into the system. Decision support systems designed using Visual Basic Net 2008 in this study can be operated properly on computers and facilitate the decision-making process in determining permanent employees at PT Siantar Top, Tbk.